PENGARUH KEPEMIMPINAN, SELF EFFICACY DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU DI SMP NEGERI 7 MANADO - Kolondam, Gerson Salomo (Sam Ratulangi University, 2017)
Abstract: the teacher is an essential component in the process of teaching and learning teachers performance indication has not been fullest due to the role of kepemimpin does not run as expected. Based on the background of this research aim to know the influence of leadership, Self efficacy and performance against the Organization's commitment to teacherstype of this research is quantitative research, data collection Methods used in this research are: observation, questionnaires, review of the literature. population studies in junior high Country 7 Manado totaled 63 teachers. Methods of analysis used was Multiple Linear RegressionThe results showed efficacy, self Leadership and organizational commitment is very influential on performance of existing teachers in JUNIOR HIGH SCHOOL the country 7 Manado. The value of the correlation coefficient r = 0.896 demonstrated that Leadership, self efficacy and organizational commitment have a very strong influence and significantly to the improved performance of teachers in JUNIOR HIGH SCHOOL In the country 7 Manado. The value of the coefficient of determination r ² = 0.802 suggests that variations in Country JUNIOR HIGH SCHOOL Leadership 7 Manado 80.2% in influence by the magnitude of efficacy, self Leadership and organizational commitment, while the remaining 19.8% in the influence of other factors Keywords: Leadership, Self Efficacy, commitment and performance of teachers Organizations